Pengembangan LKPD Indikator Alami Asam Basa dari Ekstrak Tumbuhan Kubis Ungu, Bunga Sepatu dan Kunyit - Salsabila Atazzahro; Muti'ah Muti'ah; I Nyoman Loka (FKIP University of Mataram, 2025)
This research is development research or Research and Development (R&D) which aims to produce Student Worksheets (LKPD) which are categorized as minimally feasible and practical. The research and development model used in this research is a 4D model which consists of four stages, namely defining, designing, developing and disseminating. In this research, the 4D model is limited to the development stage. Validation of the LKPD was carried out by two Chemistry Education lecturers and two Chemistry subject teachers at high school level. Data analysis in the expert validation test uses the Aiken's V Index formula. The validation results show that the LKPD validity index is generally 0.84 with a very valid validity category, which means the LKPD is very feasible based on validity. After the LKPD was tested for validation and revision, it was then tested for practicality on 25 students and 2 chemistry subject teachers. The test results show that the practical level of LKPD generally reaches 86% based on student responses and 95% based on teacher responses, both of which are classified as very practical. Based on this, this LKPD is declared very suitable for use as a learning medium regarding acid-base solutions at the high school level.